[PP.23.15] RELATIONSHIP BETWEEN PATIENT CHARACTERISTICS, RISK FACTORS, FREQUENCY OF PRIMARY ALDOSTERONISM AND THE NUMBER OF ANTIHYPERTENSIVE DRUGS IN PATIENTS WITH TRUE RESISTANT HYPERTENSION. (September 2016) - Warchol-Celinska, E.; Florczak, E.; Prejbisz, A.; Dobrowolski, P.; Szwench-Pietrasz, E.; Klisiewicz, A.; Kabat, M.; Narkiewicz, K.; Januszewicz, A.
Abstract : Objective: To assess relationship between patient characteristics, risk factors and frequency of primary aldosteronism (PA) and the number of antihypertensive drugs taken in patients with true resistant hypertension (TRHT) included in the Resist-POL study. Design and method: We evaluated 204 consecutive patients with TRHT (123 M, 81F, mean age: 48.4 ys, range 19–64ys) enrolled in the Resist-POL study. All patients were characterized by estimated glomerular filtration rate (eGFR)>60 ml/min/1, 73m2 and no history of diabetes prior to the study. Cardiovascular risk was evaluated according to ESH/ESC 2013 guidelines. In this analysis we divided patients into four groups based on the number of antihypertensive drugs taken: group 1 (3 agents, n = 41), group 2 (4 agents, n = 83), group 3 (5 agents, n = 52), group 4 (6 or more agents, n = 48). Results: In comparison to other groups, patients in the group 4 were the oldest (52.9 ± 6.9 ys, p = 0.001), whereas there was no difference in gender distribution between the groups. Patients in the group 4 were characterized by highest office, 24-hour, daytime and nighttime blood pressure levels as compared with other groups. Patients in the group 4 as compared with other groups were also characterized by highest rate of metabolic syndrome (77.1%, p = 0.020), left ventricular hypertrophy (71.7%, p < 0.001), microalbuminuria (50.0%, p = 0.001) and higher rate of patients in the category of very high added cardiovascular risk (34.4%, p = 0.001). The group 4 was also characterized by not-significantly higher frequency of PA (25%, p = 0.142) as compared to the other groups. The groups did not differ in terms of frequency of obstructive sleep apnea (OSA), whereas severe OSA was significantly more frequent in the group 3 (36.5%, p = 0.004). Conclusions: Our analysis indicate that clinical characteristics of patients enrolled to RESIST-Pol study and defined as having TRHT differed in relation to the number of antihypertensive drugs. Those taking the highest number of antihypertensive drugs were characterized by the most pronounced BP values, target organ damage, metabolic disturbances and very high added cardiovascular risk. In contrast, in patients with TRHT, increasing number of antihypertensive drugs was not indicating the significantly higher incidence of PA.